Zinc-lead mineralisation in Ganesh Himal region, central Nepal - Ghimire, J. R.; Khandka, R. K.; Chakrabarti, C. K. (Journal of Nepal Geological Society, 1996)
Carbonate hosted zinc-lead sulphide mineralisation of economic significance occurs in the Ganesh Himal region, central Nepal. The area lies in between 4,000 m and 4,900 m above msl. The mineralised bodies are situated very close to the Main Central Thrust. The mineralisation occurs in crystalline saccharoidal dolomites within a repetitive sequences of garnetiferous mica schists, quartzites, calcareous schists and amphibolites. These rocks (along with the ore) are folded into an anticlinorium and a tight synclinorium, and have suffered metamorphism of almandine-amphibolite-facies and intense deformation during Himalayan orogeny. Discontinuous bands of graphitic schists occur below the mineralised crystalline dolomites. Confined to a single carbonate stratum, the Ganesh Himal zinc-lead ore appears to be of synsedimentary origin and subsequently suffered from metamorphism. Out of six zinc-lead occurrences, only one at Lari is explored extensively. Detail investigations have confirmed more than 1 million tonnes of ore reserve averaging about 16.4% zinc, 2.5% lead and 32 grammes per tonne silver. The ore is rather simple. It consists of sphalerite, abundant pyrite, subordinate galena and pyrrhotite, and rarely chalcopyrite. X-ray diffractometry suggests possible occurrence of pyrargyrite. Ore texture indicates that the recrystallisation of sulphides took place probably at moderate to high temperature condition. Zinc lead ratio is approximately 6.13:1, with recoverable silver and low cadmium (248 ppm in average). Trace element concentration is rather insignificant. This paper is a synthesis of data on the mineral composition and trace element distribution in the Ganesh Himal zinc-lead ore.